Biometric description of gestation in the alpaca (Vicugna pacos) - Pacheco, Joel Ivan (2023)
The gestation biometrics of the alpaca (Vicugna pacos) are described. The abdominal diameter was determined monthly from 10 pregnant alpacas. In addition, uterus of 49 pregnant alpacas were collected from the Maranganí herd (Cusco, Peru) and classified by gestational age known as mating date (every 30 days from day 30 to 330 [± 15 days]). Gravid uteri were weighed and measured, allantoic and amniotic fluid was removed and measured, and fetal weight and length were determined. The results indicate a slight increase in abdominal diameter until the end of gestation, the fetus gradually increases its weight as gestation progresses, being greater from the sixth month onwards. The total length of the fetus increases from month nine. The amniotic fluid represents less than 18% of the volume of the allantoic fluid, both fluids have low volumes. An increase in fluids could be observed towards month fivem a decrease until month nine, and a subsequent increase until the delivery date.